Monetary policy and the house price boom across US Staates - Marco del Negro; Christopher Otrok (Federal Reserve Bank of Atlanta, 2005)
The authors use a dynamic factor model estimated via Bayesian methods to disentangle the relative importance of the common component in the Office of Federal Housing Enterprise Oversight's house price movements from state- or region-specific shocks, estimated on quarterly state-level data from 1986 to 2004. The authors find that movements in house prices historically have mainly been driven by the local (state- or region-specific) component. The recent period (2001–04) has been different, however: "Local bubbles" have been important in some states, but overall the increase in house prices is a national phenomenon. The authors then use a VAR to investigate the extent to which expansionary monetary policy is responsible for the common component in house price movements. The authors find the impact of policy shocks on house prices to be very small.
Keywords: C11; E58; R31; 330; housing; monetary policy; Bayesian analysis; Geldpolitik; Immobilienpreis; Bayes-Statistik; Regionaler Konjunkturzyklus; USA